Implementation Of Web-based Digital Library To Improve Learning Resource Access Services With RAD Method Approach - Risyda, Fitria; Gardenia, Yulisa; Awaludin, Muryan (Politeknik Negeri Lhokseumawe, 2025)
The advancement of digital technology opens up opportunities for libraries to improve their services, including at the Universitas Dirgantara Marsekal Suryadarma (UNSURYA) Library. Fast, flexible, and integrated access are the main needs of the academic community. However, the system at the UNSURYA library currently has limitations such as limited operating hours and physical constraints in managing digital collections such as e-books, digital books, theses, and dissertations. This study aims to develop a digital library that can improve accessibility and user experience in accessing learning resources at the UNSURYA campus library. Application development using the Rapid Application Development (RAD) method, functional testing of the application using blackbox testing and usability testing to see user responses to the application that has been developed. The results of the usability testing questionnaire using the System Usability Scale (SUS) Score calculation showed a value of 80, the conversion of this value shows the